2010
DOI: 10.1016/j.ccr.2009.11.021
|View full text |Cite
|
Sign up to set email alerts
|

IAP Regulation of Metastasis

Abstract: SUMMARY Inhibitor-of-Apoptosis (IAP) proteins contribute to tumor progression, but the requirements of this pathway are not understood. Here, we show that intermolecular cooperation between XIAP and survivin stimulates tumor cell invasion and promotes metastasis. This pathway is independent of IAP inhibition of cell death. Instead, a survivin-XIAP complex activates NFκB, which in turn leads to increased fibronectin gene expression, signaling by β1 integrin(s), and activation of cell motility kinases, FAK and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
264
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(282 citation statements)
references
References 56 publications
13
264
1
4
Order By: Relevance
“…This is consistent with recent studies that implicated survivin in invasion and metastasis. 24 In summary, this manuscript demonstrates that in the absence of K-Ras, survivin ubiquitination levels are increased, leading to its degradation by the proteasome, and suggests that this important biochemical link between mutant K-Ras, and the stability of survivin contributes to K-Ras-driven malignant transformation. its targeted expression in skin predispose mice to UV-induced tumors.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This is consistent with recent studies that implicated survivin in invasion and metastasis. 24 In summary, this manuscript demonstrates that in the absence of K-Ras, survivin ubiquitination levels are increased, leading to its degradation by the proteasome, and suggests that this important biochemical link between mutant K-Ras, and the stability of survivin contributes to K-Ras-driven malignant transformation. its targeted expression in skin predispose mice to UV-induced tumors.…”
Section: Discussionmentioning
confidence: 67%
“…Recent studies have demonstrated, as is the case for K-Ras, that survivin is also involved in other hallmarks of cancer such as invasion and metastasis. 24 However, it is not known whether K-Ras contributes to the maintenance of the high levels of survivin in human tumors, and whether this contributes to mutant K-Ras-mediated malignant transformation…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, survivin is a member of the inhibitor of apoptosis gene family that mediates several antiapoptotic functions (6,7), and its expression is associated with disease progression and poor prognosis in many cancer types (8). Moreover, survivin has also been implicated in the development of resistance to apoptosisinducing agents (9) and promotion of metastasis (10). We integrated the survivin promoter into the VISA system to selectively enhance the expression of a therapeutic gene, BikDD, a mutant form of the proapoptotic Bcl2 interacting killer (Bik), to generate survivin-VISA-BikDD (SV-BikDD) and showed that systemic treatment with SV-BikDD DNA in liposome complexes controlled tumor growth and significantly prolonged survival in immunocompromised mice with metastatic human lung cancer and produced virtually no toxicity compared with the CMV promoter vector (5).…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Fig. 6, 1-3 Based on research by Mehrotra et al [43], the activation of the cell motility kinases focal adhesion kinase (FAK) and c-Src tyrosine kinase (c-Src) by NF-κB contributes to cancer progression and metastasis, and the activity of NF-κB is related to survivin [59]. Activation of survivin is due to the mutation of WnT signaling leading to further activation of β-Catenin.…”
Section: Cell Invasion Studymentioning
confidence: 99%